Time Management In Education - Radjabova Gavkhar Umarovna (Global Scientific Publishing, 2025)
This article examines time management as a tool for improving selforganization. A survey revealed that students understand time management, but most experience a lack of free time and struggle to manage their time effectively. Students are interested in learning time management and want to master the skills of selforganization in their studies.
Keywords: time management; student; independent work